2009
DOI: 10.1097/mpa.0b013e31819f65c3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Small Pancreatic Cancer by Endoscopic Balloon-Catheter Spot Pancreatography

Abstract: Balloon spot pancreatography is an essential tool for the diagnosis of small ductal pancreatic cancer, and it also makes it possible to locate CIS lesions of the branch ducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Focal ductal branch dilatations and cystic lesions around the MPD were also observed (Figure 5). 56, 60, 61, 62 Recently, Kikuyama et al . reported that three out of 14 cases with PCIS had a high degree of fatty changes of the pancreatic parenchyma adjacent to PCIS, which were recognized on CT 63.…”
Section: Diagnosis Of Pcismentioning
confidence: 99%
“…Focal ductal branch dilatations and cystic lesions around the MPD were also observed (Figure 5). 56, 60, 61, 62 Recently, Kikuyama et al . reported that three out of 14 cases with PCIS had a high degree of fatty changes of the pancreatic parenchyma adjacent to PCIS, which were recognized on CT 63.…”
Section: Diagnosis Of Pcismentioning
confidence: 99%
“…Especially for stage 0 pancreatic cancer, which is carcinoma in situ, localized main pancreatic duct stricture is often the only image finding, and detailed evaluation of the pancreatic duct image by ERP and subsequent pancreatic juice cytology are extremely important for the diagnosis. It has been reported that detailed evaluation of pancreatic duct images, including branch pancreatic ducts by endoscopic balloon catheter spot pancreatography, was useful for the diagnosis of small pancreatic cancer [84]. In addition, the usefulness of serial pancreatic juice cytology using an endoscopic nasopancreatic drainage catheter in the diagnosis of pancreatic carcinoma in situ has been reported, and the sensitivity was excellent at 72.2-100% [85][86][87].…”
Section: Diagnostic Performance Of Ercp For Pancreatic Cancermentioning
confidence: 99%
“…The precise pancreatogram should be carried out for cases with indirect abnormal findings in PD. Endoscopic retrograde cholangiopancreatography (ERCP) and facilitating further examinations, such as cytology using pancreatic juice, has already been established for the early diagnosis of PC [6]. Recently, institutions have tended to perform magnetic resonance cholangiopancreatography (MRCP) for the diagnosis of PC due to the concern of post-ERCP pancreatitis (PEP).…”
Section: Introductionmentioning
confidence: 99%